2019
DOI: 10.1021/acs.jafc.8b07109
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gut Microbiota by Soybean 7S Globulin Peptide That Involved Lipopolysaccharide–Peptide Interaction

Abstract: Soybean protein exhibits nutritional significance for the control of metabolic syndrome, and evidence suggests that gut microbiota are implicated in the control of metabolic disorders. This study aimed to investigate the modulation of pepsin-released peptides of soybean 7S globulin on gut microbiota and possible association between changes of gut microbiota composition and lipopolysaccharide (LPS)−peptide interaction. In vitro fermentation experiments showed that the extension region (ER) fragments of soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…It was reported some positive correlations between Blautia spp . and microbial products such as long-chain triglycerides [70] and short chain fatty acids (SCFAs) [71], and parameters like BFG, insulin level, HOMA-IR, and weight loss [56,72]. A decreased abundance of Blautia coccoides / Eubacterium rectale was found in T1D children and was linked to intestinal disintegrity [73], while a randomized crossover study in healthy adults reported a reduced abundance of Blautia genus after prebiotic supplementation [74].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported some positive correlations between Blautia spp . and microbial products such as long-chain triglycerides [70] and short chain fatty acids (SCFAs) [71], and parameters like BFG, insulin level, HOMA-IR, and weight loss [56,72]. A decreased abundance of Blautia coccoides / Eubacterium rectale was found in T1D children and was linked to intestinal disintegrity [73], while a randomized crossover study in healthy adults reported a reduced abundance of Blautia genus after prebiotic supplementation [74].…”
Section: Discussionmentioning
confidence: 99%
“…Soybean also contains bioactive peptides or hydrolysates with positive impacts on body weight, and their effects on gut microbiota composition in obesity have been reported. Research investigating the modulatory effects of pepsin-released peptides of soybean 7S globulin on gut microbiota indicated that soybean 7S globulin peptide is involved in lipopolysaccharide-peptide interaction effects of gut microbiota functions related to obesity [ 49 ]. The soybean 7S globulin selectively suppressed pro-inflammatory gram-negative bacteria, and also promoted the production of SCFAs due to increased Lachnospiraceae and Lactobacillaceae relative abundance [ 49 ].…”
Section: Gut Microbiota Obesity and Hydrolysates/bioactive Peptidesmentioning
confidence: 99%
“…Research investigating the modulatory effects of pepsin-released peptides of soybean 7S globulin on gut microbiota indicated that soybean 7S globulin peptide is involved in lipopolysaccharide-peptide interaction effects of gut microbiota functions related to obesity [ 49 ]. The soybean 7S globulin selectively suppressed pro-inflammatory gram-negative bacteria, and also promoted the production of SCFAs due to increased Lachnospiraceae and Lactobacillaceae relative abundance [ 49 ]. Furthermore, a high amount of 7S globulin in soy milk promoted the growth of the Bacteroides-Prevotella group in obese men [ 50 ], while soybean pepsin-hydrolysate conglycinin maintained a healthy gut microbial community by inhibiting the growth of E. coli in mice [ 51 ].…”
Section: Gut Microbiota Obesity and Hydrolysates/bioactive Peptidesmentioning
confidence: 99%
“…The benefits of ⊎-conglycinin in reducing obesity and metabolic diseases have attracted the attention of researchers. [3][4][5] However, as a most important protein allergen, ⊎-conglycinin induces food allergic reactions in humans. 6 Therefore, reduction or even complete elimination of sensitization of ⊎-conglycinin will expand its utilization in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…β‐Conglycinin is the main storage protein in soybeans, and it accounts for 40% of total soybean protein. The benefits of β‐conglycinin in reducing obesity and metabolic diseases have attracted the attention of researchers 3‐5 . However, as a most important protein allergen, β‐conglycinin induces food allergic reactions in humans 6 .…”
Section: Introductionmentioning
confidence: 99%